2014
DOI: 10.1007/s00216-014-8037-8
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific qualitative and quantitative analysis of the N- and O-glycoforms in recombinant human erythropoietin

Abstract: Recombinant human erythropoietin (rhEPO) has been extensively used as pharmaceutical product for treatment of anemia. Glycosylation of rhEPO affects the biological activity, immunogenicity, pharmacokinetics and in vivo clearance rate of rhEPO. Characterization of the glycosylation status of rhEPO is of great importance for its quality control. In this study, we established a fast and comprehensive approach for reliable characterization and relative quantitation of rhEPO glycosylation, which combines multiple e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…[32][33][34] Recently, a few groups have utilized LC/MS-based platform to determine glycosylation sites with glycan microheterogeneity of the first generation EPO. 13,35,36 However, site-specific glycosylation analysis is still in its infancy due to the absence of proper technologies and methods. No doubt site-specific profiling will be a powerful platform to provide all of the information available with the localization of glycosylation with glycan heterogeneity.…”
Section: 32mentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] Recently, a few groups have utilized LC/MS-based platform to determine glycosylation sites with glycan microheterogeneity of the first generation EPO. 13,35,36 However, site-specific glycosylation analysis is still in its infancy due to the absence of proper technologies and methods. No doubt site-specific profiling will be a powerful platform to provide all of the information available with the localization of glycosylation with glycan heterogeneity.…”
Section: 32mentioning
confidence: 99%
“…It should come as no surprise, therefore, that MS has contributed significantly to recent progress towards understanding the role of the glycome in biotherapeutic glycoproteins including mAbs, recombinant proteins (such as EPOs), therapeutic enzymes, and fusion proteins. 4,[10][11][12][13][14][15][16] This review will cover the current state of the arts in MS-based analytical platforms for comprehensive characterization of EPO glycosylation in respect of N-and O-glycome, and site-specific glycoform profiling.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometric studies on rEPO and its next‐generation derivatives have been an ongoing endeavor for both in‐depth characterization of glycoforms in pharmaceutical products as well as alternative detection methods in sports drug testing. Okano et al .…”
Section: Peptide Hormones Growth Factors and Related Substancesmentioning
confidence: 99%
“…Mass spectrometric studies on rEPO and its next-generation derivatives have been an ongoing endeavor for both in-depth characterization of glycoforms in pharmaceutical products [87] as well as alternative detection methods in sports drug testing. Okano et al utilized the fact that darbepoetin alpha comprises a modified protein backbone, enabling the generation of a peptide of unique amino acid composition, which serves as target structure for doping controls.…”
Section: Peptide Hormones Growth Factors and Related Substances Erytmentioning
confidence: 99%
“…3,[6][7][8][9] Glycan is a major structural moiety that has important effects on the pharmacokinetics and pharmacodynamics of EPO analogues such as darbepoetin alfa and epoetin alpha and beta. [10][11][12][13] The structure of glycan in EPO plays an important role in various biological activities. First, several studies have shown that sialic acid capping of the terminal galactose residue prevents hepatic clearance of EPO.…”
Section: Introductionmentioning
confidence: 99%